ANALISIS RISIKO DAN PENGELOLAAN RISIKO PADA KONTRAK MUDHARABAH DAN MUSYARAKAH DALAM PERBANKAN SYARIAH - Dayu, Wulan; Anggara, Windu; Sudiarti, Sri; Marliyah, Marliyah (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
Mudharabah and musyarakah contracts are the two main forms of sharia banking products and services used to support financing and investment in business according to sharia rules. This study aims to conduct an in-depth analysis of the risks associated with the implementation of mudharabah and musyarakah contracts in the Islamic banking business, as well as analyze effective approaches to managing these risks. The research method used is a qualitative approach with in-depth interviews and document analysis from leading Islamic banks. The results of the analysis show that mudharabah and musyarakah contracts have unique risks compared to conventional banking products. The main risks identified include financial risk, operational risk, legal and sharia risk, and reputation risk. However, there are some differences in the type of risk involved in these two contracts. Risk management on mudharabah and musyarakah contracts needs to be done carefully and proactively to ensure the sustainability of the sharia banking business. Some of his practices include implementing good governance, selecting the right business partners, portfolio diversification, and close monitoring of project implementation and the use of investment funds. The implications of the results of this research are expected to assist Islamic banks in improving operational sustainability, facing challenges, and achieving their business goals by minimizing the risks that may arise in the implementation of this product.